Pengaruh E-Service Quality Terhadap Repurchase Intention Melalui E-Satisfaction: Studi Pada Pengguna Platform Sociolla Tahun 2023 - Luyanny Luyanny; William Widjaja (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
The rise of the trade in fake cosmetics and skincare in various well-known e-commerce makes consumers more selective in purchasing cosmetic and skincare products. However, Sociolla as the number one well-known beauty store in Indonesia comes with its e-commerce platform that specifically sells cosmetic and skincare products from various well-known product brands and is able to stay in first place in the beauty product category in Top Beauty-Commerce. This trend can be seen from the increasing frequency of repeated transactions on the Sociolla platform. This study aims to determine the effect of the relationship between electronic service quality (E-Service Quality) and repurchase intention (Repurchase Intention) through electronic satisfaction (E-satisfaction) as a mediation variable. This research is quantitative. The data collection technique was carried out by distributing a 4-level linear scale statement questionnaire. Samples were taken using Non-Probability Sampling techniques with data analysis techniques using Smart PLS tools. The respondents involved were 160 respondents who met the criteria for having made purchases on the Sociolla platform twice. The results showed that good E-Service Quality skills increased E-Satisfaction which led to Repurchase Intention by Sociolla platform users. This shows that E-Satisfaction effectively acts as a mediation between E-Service Quality and Repurchase Intention.